1989
DOI: 10.1177/00220345890680051701
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Model Cavity Method for Assessing Antibacterial Properties of Dental Restorative Materials

Abstract: A new in vitro method for assessing the antibacterial properties of dental restorative materials is described with ratios of test material/culture medium volume aiming to simulate conditions around a restoration in vivo. Antibacterial activity is determined by the reduction in optical density of the test culture relative to controls. The method was used for assessment of the antibacterial activity of five dental materials of different composition against five oral bacteria. Release of zinc and fluoride from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…These results confirm the findings of previous studies [Herrera et al, 1999;Palenik and Setcos, 1996]. The growth-inhibitory effect of GICs has been attributed to the release of fluoride [Forss et al, 1991;Meryon and Johnson, 1989;Yap et al, 1999]. However, only a few studies showed a direct correlation between fluoride release and antibacterial properties of GICs [Friedl et al, 1997;Loyola Rodriguez et al, 1994;Palenik et al, 1992].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results confirm the findings of previous studies [Herrera et al, 1999;Palenik and Setcos, 1996]. The growth-inhibitory effect of GICs has been attributed to the release of fluoride [Forss et al, 1991;Meryon and Johnson, 1989;Yap et al, 1999]. However, only a few studies showed a direct correlation between fluoride release and antibacterial properties of GICs [Friedl et al, 1997;Loyola Rodriguez et al, 1994;Palenik et al, 1992].…”
Section: Discussionsupporting
confidence: 88%
“…When using eluates, the arbitrarily selected extraction conditions for the restorative materials may influence the results [Meryon and Johnson, 1989]. In addition, the BSWM assay is suitable for longterm studies because time of exposing bacterial suspensions to dental materials is not limited by restrictions of the experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…Pronounced antimicrobial effects are found in in vitro studies with glass ionomer cement (GIC) [Tobias et al, 1985;Meryon and Johnson, 1989;Paleniketal., 1992;Loyola-Rodriguez et al, 1994], Some in vivo studies showed less cariogenic plaque adjacent to GIC restorations [Berg et al, 1990;Forss et al, I99la;Hallgren et al, 1994], although plaque inhibition was not always confirmed [van Dijken et al, 1991;Forss et al, 1991b]. A proportional reduction of mutans streptococci in plaque and the facilitation of remin eralization of enamel lesions as a result of fluoride release [McLean and Wilson.…”
mentioning
confidence: 99%
“…During the reopening of the cavity and removal of remaining decayed dentine, the mechanical procedures may injure the pulp, increasing the risk of pulp exposure and submit the patient to an additional appointment 10 . Regarding the sealing material, glass-ionomer cement (GIC) has proved to have antimicrobial effects [16][17][18] . Some in vivo studies have shown less cariogenic plaque adjacent to GIC restorations 19 and other studies have demonstrated that enamel lesions can be easier remineralized as a result of fluoride release 20 and consequently diminish the risk for recurrent caries at cavity enamel margins 21 .…”
Section: Discussionmentioning
confidence: 99%